Recent Progress in Bioactive Substance Encapsulation System Based on Electrospinning and Its Application in Antimicrobial Food Packaging - REN Jie, TAN Zhongmei, TIAN Zihao, WU Gaoyun, LIU Yongchen, WANG Hao, JIANG Zhanmei, MA Jiage, HOU Juncai (Shipin Kexue)
The contamination of foods by foodborne pathogenic and spoilage microorganisms is one of the major causes of foodborne diseases. Therefore, ensuring food quality and extending its shelf life are urgent concerns for researchers. The application of electrospinning technology to encapsulate bioactive substances in antimicrobial food packaging is an effective method to ensure food safety. First, this article reviews the basic principle of electrospinning, the types of electrospinning used for antimicrobial food packaging, the factors influencing electrospinning, and the electrospinning materials used in antimicrobial food packaging. Next, the bioactive substances encapsulated in electrospun nanofibers and the co-encapsulation systems for bioactive substances based on electrospinning are summarized systematically. Finally, we examine recent progress in the application of electrospun nanofibers encapsulating bioactive substances in antimicrobial packaging for meat, dairy products, fruits and vegetables, and we also discuss the challenges and future trends for antimicrobial food packaging based on electrospinning. The aim of this study is to provide theoretical support and a basis for the application of electrospun nanofibers encapsulating bioactive substances to effectively inhibit foodborne pathogens and spoilage microorganisms in the food industry.